Age-specific association of migraine with cryptogenic TIA and stroke: Population-based study. (27th October 2015) - Li, Linxin; Schulz, Ursula G.; Kuker, Wilhelm; Rothwell, Peter M.
Abstract : Objective: To determine whether there is an association between previous migraine and cryptogenic TIA or ischemic stroke at older ages. Methods: We determined the age-specific associations of history of migraine and Trial of Org 10172 in Acute Stroke Treatment (TOAST) subtype of TIA and ischemic stroke in a population-based cohort study (Oxford Vascular Study; 2002–2012). Results: Among 1, 810 eligible patients with TIA or ischemic stroke, 668 (36.9%) had cryptogenic events, of whom 187 (28.0%) had previous migraine. Migraine was more commonly associated with cryptogenic events than with those of known etiology (odds ratio [OR] 1.73, 95% confidence interval [CI] 1.38–2.16, p < 0.0001; cardioembolic 2.00, 1.50–2.66, p < 0.0001; large artery 1.75, 1.20–2.53, p = 0.003; small vessel 1.32, 0.95–1.83, p = 0.096). The association of migraine with cryptogenic events was independent of age, sex, and all measured vascular risk factors (RFs) (adjusted OR 1.68, 1.33–2.13, p < 0.0001) and was strongest at older ages (<55 years, OR 1.11, 0.55–2.23; 55–64 years, 1.48, 0.83–2.63; ≥65 years, 1.81, 1.39–2.36) and in patients without vascular RFs (0 RFs OR 2.62, 1.33–5.15; 1 RF 2.01, 1.35–3.01; 2 RFs 1.80, 1.21–2.68; 3 RFs 1.21, 0.71–2.07; 4 RFs 0.92, 0.28–2.99). Results were consistent for migraine with or without aura and for analyses excluding TIA or stratified by sex or vascular territory of event. Conclusions: In this population-based study of stroke etiology stratified by age, migraine was most strongly associated with cryptogenic TIA and ischemic stroke, particularly at older ages, suggesting a causal role or a shared etiology.